The Relationship Between Employee Job Satisfaction, Perceived Customer Satisfaction, Service Quality, and Profitability in Luxury Hotels in Kuala Lumpur - Singh, Harcharanjit; Saufi, Roselina Ahmad; Tasnim, Rahayu; Hussin, Maizaitulaidawati (Prabandhan: Indian Journal of Management, 2017)
The research examined the relationship between employee job satisfaction, perceived customer satisfaction, service quality, and profitability in five hotels in Kuala Lumpur, Malaysia. This researchÂ explored the relationship between employee job satisfaction, perceived customer satisfaction, service quality, and profitability in the luxury hotels in Kuala Lumpur. It is common knowledge that hoteliers are effectively looking for new approaches in order to increase their service values through their service quality offerings. High rate service quality can only be attained through effective and efficient hotel operations that can surpass customers’ expectations and finally increase firm profitability. There were around 150 respondents from the top and middle managers of the hotels in Kuala Lumpur. The period of the study was from January to December 2015. The data was analyzed using the SPSS statistical package. The research found that higher employee job satisfaction increases service quality and this increases hotels’ profit. On the other hand, employee job satisfaction generates higher customer satisfaction and increases hotel profitability through future sales and customer positive goodwill. The paper ended with a discussion on implications and limitations of the research and some directions for future studies are suggested.